2020
DOI: 10.26717/bjstr.2020.26.004360
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of Ectoparasites in Dairy Calves Reared by Smallholder Farmers in Central Areas of Ethiopia

Abstract: Ectoparasites are one of the major health constraints of cattle production and are usually associated with huge economic losses in Ethiopia. A cross-sectional and clinical investigation was carried out in urban and periurban dairy farms in different central areas of Ethiopia to determine the infestation of external parasites and its attributable risk factors in dairy calves. Thus, a total of 157 dairy calves were clinically examined for ectoparasite infestations in central Oromiya. Results from data analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…This study suggested that overall prevalence of ectoparasites of dairy cows was 69%. This finding was higher than the reports of Urge B [20], who reported 40.76% prevalence of ectoparasites. This difference might be due to the presence of various factors like veterinary service delivery system, feeding and management, animal husbandry practice, and variation in the geographical locations.…”
Section: Discussioncontrasting
confidence: 80%
“…This study suggested that overall prevalence of ectoparasites of dairy cows was 69%. This finding was higher than the reports of Urge B [20], who reported 40.76% prevalence of ectoparasites. This difference might be due to the presence of various factors like veterinary service delivery system, feeding and management, animal husbandry practice, and variation in the geographical locations.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition to ticks, other blood-feeding parasites such as lice and fleas have also been implicated as potential vectors for brucellosis. A study conducted in Ethiopia found that lice collected from cattle were positive for Brucella DNA, suggesting their potential role in transmitting the bacteria [ 88 ]. Similarly, a study conducted in Mexico detected Brucella DNA in fleas collected from dogs [ 55 ].…”
Section: Discussionmentioning
confidence: 99%